Extração de óleo residual das tortas de polpa e amêndoa da macaúba (Acrocomia aculeata) utilizando como solvente o etanol e isopropanol - Fabiana Aparecida da Fonseca (2016)
About at diversifying products, and industrial sustainability, different industries have shown interest in exploring and using new renewable sources of plant origin, such as industrial raw material. One of the raw materials of industrial interest are the larest sources of oleaginous plants, which have various applications on the chemical, food, cosmetics, among others. In this sense, the fruit of macauba has emerged as a promising alternative to oilseeds traditionally exploited, mainly due its high oil yield per hectare of fruit. The processes used for the extraction of oils from macauba are mechanical pressing, widespread for its efficiency in extraction oil, followed by solvent extraction in order to recover the residual oil present in macauba meal after pressing. Industrially, the solvent used for oil extraction is n-hexane. However, this solvent is toxic and unsustainable because it comes from non-renewable source. Thus, the search for solvents to replace n-hexane for the extraction of vegetable oils with the same efficiency, safety and sustainability is of great relevance. In this sense, ethanol, and other alcohols and mixtures of solvents have been investigated as a possible alternative to n-hexane. Based on these considerations, this project aims to study the residual oil extraction macauba meal pulp and macauba meal almond as a solvent pure ethanol and isopropanol, as well as different mixtures with water. Parameters as macauba meal proportion: solvent, water content in solvents and process temperature will be investigated for the influence on the yield and kinetics of extraction of oils, using experimental design. In general, the extraction of exhibited satisfactory results obtained with yields above 80% in most cases. In setting employing proposed kinetic models indicated that the model that best describes a model 2-stage and second-order. This work aims to contribute to a better understanding of the extraction of the vegetable oil extration process when different solvents are used, even in the presence of process water.